Disseminated mpox in an immunocompromised patient in DR Congo: a call for a shift from disease-focused to person-centred outbreak response - Bugeme, Patrick Musole; Bugale, Patrick Kazuba; Mashauri, Joël Zigashane; Kapalata, André Ishara; Bugwaja, Levi; Mukika, Trust Faraja; Shangula, Salomon Mashupe; Sebiyoyo, Philémon Hodari; Barungu, Daniel Buuma; Kasi, Willy; Bengehya, Justin; Katoto, Patrick D M C; et al. (The Lancet infectious diseases, 2025)
In August, 2024, a male nurse aged 32 years, who had treated patients with suspected mpox, presented at the mpox treatment centre at the Uvira Referral Hospital after a 2-day motorbike transfer from a rural hospital due to worsening condition despite 3 weeks of supportive treatment. Additionally, while HIV testing and case management are available for free at the Uvira Referral Hospital through the national HIV programme, they are not integrated into the standard mpox treatment centre care package. Investments in universal health coverage and local capacity building are essential for addressing complex patient needs during epidemics and beyond. 3–5 Integrated models would enable comprehensive care, timely diagnostics, appropriate therapies, and tailored nutritional support, ensuring better outcomes.